2019
DOI: 10.3390/ani10010045
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chromium Nanoparticles and Chromium Picolinate in the Diet of Chickens on Levels of Selected Hormones and Tissue Antioxidant Status

Abstract: Simple Summary:We have postulated that supplementation with Cr can increase serotonin levels and improve the antioxidant status of chickens, with no adverse effect on the secretion of other hormones. Obtaining such results may be beneficial in high-density rearing of poultry exposed to many stressors. The studies compared the effects of two forms of Cr (Cr-Pic and Cr-NP) found at two doses 3 and 6 mg/kg. It was found that at the dose of 3 mg/kg, the expected beneficial results can be obtained (increase in sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…According to Yang et al [43] and Sontakke and Tare [44], ROS are involved in the resorption of Ca and P from bone. Our previous research [5] showed that Cr may have a pro-oxidative effect, and therefore the reduction in P levels noted in the bones may also be associated with oxidative stress generated by Cr. Stępniowska et al [5] noticed that the addition of 6 mg/kg Cr to the diet of chickens, increased lipid peroxidation in both the liver and breast muscle, as evidenced by increased LOOH levels.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…According to Yang et al [43] and Sontakke and Tare [44], ROS are involved in the resorption of Ca and P from bone. Our previous research [5] showed that Cr may have a pro-oxidative effect, and therefore the reduction in P levels noted in the bones may also be associated with oxidative stress generated by Cr. Stępniowska et al [5] noticed that the addition of 6 mg/kg Cr to the diet of chickens, increased lipid peroxidation in both the liver and breast muscle, as evidenced by increased LOOH levels.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous research [5] showed that Cr may have a pro-oxidative effect, and therefore the reduction in P levels noted in the bones may also be associated with oxidative stress generated by Cr. Stępniowska et al [5] noticed that the addition of 6 mg/kg Cr to the diet of chickens, increased lipid peroxidation in both the liver and breast muscle, as evidenced by increased LOOH levels. Also the changes in the activity of antioxidant enzymes noted in this study were the body's response to the intensification of oxidative processes due to the addition of Cr to the diet.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations